Literature Review: Use of Technology in the Learning Process at High School Level - Safi'i, Muhammad; Lubis, M. Joharis; Hutagalung, Surya Masniari (PT. Riset Press International, 2025)
In this era of digitalization, there have been major changes in education, especially with the integration of technology into the world of education. As an advanced stage of formal education, high school plays an important role in integrating technology into the teaching-learning process. Various studies show the great potential of technology to enrich student learning experiences, improve access to educational resources, and improve teaching efficiency. The study used the literature review method, combining the results of several related studies into a new topic. From the review, it was found that the use of technology in high schools involves a variety of digital infrastructures and programs, such as Zoom, Canva, digital education (E-Learnings), Google Classroom, Google Sites, Magic School, Kahoot, E-Ujian, video conference, electronic report (e-Rapot), and WhatsApp Application. The main advantage of technology is its ability to make teaching more exciting and interactive for learners. However, the challenge is the inequality of connectivity related to technology. Students who do not have electronic devices or internet connectivity risk being left behind, creating differences or imbalances in learning opportunities.